(untitled) (Social Science Review, 2024)
The 2022 Russian invasion of Ukraine has had profound implications for global peace and security. This explorative paper aims to delve into the collective security debate to analyse the violent conflict between Russia and Ukraine, particularly considering the role of NATO’s expansion in shaping this crisis. By examining the potential for nuclear escalation and its wider impact on global dynamics, this paper highlights the grave threat posed by the deployment of nuclear weapons, emphasizing the urgency of taking immediate action to avert catastrophic consequences. It also explores the far-reaching consequences of the conflict, encompassing disruptions in the movement of people and goods, economic ramifications such as escalating oil prices and inflation, and the pressing concerns surrounding global food security. By leveraging diverse secondary sources with the authors’ introspective criticalities, this paper discusses the importance of diplomatic efforts, multilateral cooperation, and nuclear disarmament as crucial elements in resolving the conflict and preserving international stability. Social Science Review, Vol. 40(2), December 2023 Page: 185-204